Preliminary study of lecturer competency analysis in learning at health universities - Novriyanti Achyar; Nurhizrah Gistituati; Hendri Budi Utama; Luthfiani Luthfiani; Indra Jaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to reveal the results of the analysis regarding lecturer competence in practical learning at universities in the health sector. Lecturer competence is the variable studied with indicators including pedagogical competence, personality competence, social and professional competence. The method used in this research uses a descriptive quantitative approach. The data collection technique uses primary data from a sample of 50 students with a sampling technique using cluster sampling. Data collection uses instruments that have passed the validity and reliability process. Data analysis in this study used descriptive analysis techniques. The results of this research indicate that overall, the average lecturer competency of all indicators is categorized as adequate with a score of 2.94 and an achievement level of 73.60. Only one of the four lecturer competency indicators, namely personality competency, received good criteria, while the other three received sufficient categories.